Emergência de capim-carrapicho e picão-de-flor com diferentes profundidades de semeadura em duas épocas - Giancotti, Paulo Roberto Fidelis [UNESP]; de Souza, Marcelo Claro [UNESP]; Parreira, Mariana Casari [UNESP]; Alves, Pedro Luís da Costa Aguiar [UNESP] (My University, 2011)
With the purpose to study the emergence of Cenchrus echinatus L.and Cosmos sulphureus Cav. in response to time and depth of sowing, two experiments were conducted in uncontrolled environmental conditions in the months of June and September 2009. Cenchrus echinatus L.and Cosmos sulphureus Cav seeds were sown at different depths (0, 1, 3, 5, 7 and 9 cm). The experiments were conducted in pots, with five replications of 50 seeds per pot, followed by evaluation of the emergence percentage and emergence speed index (ESI). The highest percentage of emergency and higher EVR were observed up to 5 cm depth and the species Cosmos sulphureus Cav. was more sensitive to temperature variations due to the time of sowing of the species C. equinatus.
Emergence of Cenchrus echinatus L. and cosmos sulphureus cav. with different sowing depths in two seasons
Keywords: Cenchrus echinatus; Cosmos sulphureus; Germination; Reproductive Biology